Effects of COVID-19 on E-learning at Hassan II University of Casablanca, students: Results of survey conducted on 9,439 students - Khalid LAHYANI; Ghizlane DIAB; Taoufik AIT BOUCHGOUR; Othmane BENAMMAR (Communications of International Proceedings, 2021)
The COVID-19 pandemic has changed education forever. It has resulted in Universities shut all across the world. In response to the emerging and ever solution to the COVID-19 epidemic, universities have innovated by creating new elearning plateforms. The purpose of this paper is to conduct a study on 9,439 students of Hassan II University of Casablanca, in particular to verify whether this was their first experience in e-learning? the difficulties encountered when using the new platform? How they connect to this platform? As well as a vision of the different platforms that students use during this period and if the objectives have been achieved and the degree of student satisfaction of the new elearnig plateform.
Keywords: e-learning; higher education; COVID-19; coronavirus; Hassan II University of Casablanca